The wolf at the door - Higgins, Jack, 1929- (New York : G.P. Putnam's Sons, 2010)
Who's knocking off members of a special intelligence unit known as the prime minister's private army? Only Sean Dillon has a clue.
Keywords: Dillon, Sean (Fictitious character) -- Fiction; Ferguson, Charles (Fictitious character) -- Fiction; Secret service -- Fiction; Assassins -- Fiction; England -- Fiction; Suspense fiction; Spy stories